Discussion of a Prediction of Business Failure Using Accounting Data - Kinney, William R. (Journal of Accounting Research, 1973)
William R. Kinney, Jr., Discussion of a Prediction of Business Failure Using Accounting Data, Journal of Accounting Research, Vol. 11, Empirical Research in Accounting: Selected Studies 1973 (1973), pp. 183-187